2007
DOI: 10.1016/j.jvs.2006.11.048
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular filtration rate after left renal vein division and reconstruction during infrarenal aortic aneurysm repair

Abstract: LRV division during AAA repair was associated with larger aneurysms and preoperative subclinical renal function impairment. In these patients, LRV reconstruction was associated with the maintenance of preoperative renal functional status without significantly lengthening of operative time or increasing the complications from surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 28 publications
0
16
1
Order By: Relevance
“…3,[6][7][8][9]12,[18][19][20] The long-term effect of left renal division remains debatable. 8,21,22 Although West et al 8 found renal vein division to be associated with pulmonary complications and renal insufficiency, it was not associated with any RD or death in the present series. Every effort is made in our institution to avoid left renal vein division if at all possible.…”
Section: Discussioncontrasting
confidence: 60%
“…3,[6][7][8][9]12,[18][19][20] The long-term effect of left renal division remains debatable. 8,21,22 Although West et al 8 found renal vein division to be associated with pulmonary complications and renal insufficiency, it was not associated with any RD or death in the present series. Every effort is made in our institution to avoid left renal vein division if at all possible.…”
Section: Discussioncontrasting
confidence: 60%
“…More recently, there have been further recommendations that the LRV should be reconstructed after temporary division. 16 However, it has been our experience that re-anastomosis is not only unnecessary, but increases both operative time and potential blood loss in an already complex operation. The benefit of LRVDAL on these aspects of the perioperative experience cannot be assessed from this study since we have no valid personal comparison to surgery without this maneuver.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-two cirrhotic patients were classified as CTP class A and two as CTP class B. Median MELD score was 8 (range, [6][7][8][9][10][11][12][13][14]. Seventeen patients had a MELD Ͻ10, and seven a MELD Ն10.…”
Section: Resultsmentioning
confidence: 99%
“…12 Cirrhotics were further stratified according to the CTP (Table I), and the MELD score that includes the international normalized ratio (INR), serum creatinine, and serum bilirubin. 13 The original mathematical formula is: 9.57 ϫ log e (creatinine) ϩ 3.78 ϫ log e (total bilirubin) ϩ 11.2 ϫ log e (INR) ϩ 6.43…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation